2021
DOI: 10.1177/10711007211002807
|View full text |Cite
|
Sign up to set email alerts
|

Talonavicular Joint-Sparing 3D Printed Navicular Replacement for Osteonecrosis of the Navicular

Abstract: Pathology of the navicular can be a difficult entity to treat, particularly when the injury has progressed to osteonecrosis. While various nonoperative and operative modalities have been described, the emerging field of additive manufacturing has become a potential solution to this difficult problem in certain scenarios. While these implants have largely been used for fusion in the past, the concept of joint sparing with 3D printed implants is also emerging, and this case highlights a patient treated with a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…At the 5-year follow-up, the longest recorded follow-up in the literature, the patient was found to exhibit osseous integration on radiographic imaging with Patient Reported Outcome Measures indicating high function and negligible pain 6 . Adams and Danilkowicz 7 implemented the use of a custom, 3D printed titanium implant for talonavicular joint salvage in the setting of navicular fracture with maintained radiographic alignment, successful arthrodesis to the cuneiforms, function of the talonavicular joint, and continued employment at 4 years of follow-up. Dekker et al 8 reported on 15 consecutive patients who received a custom, 3D printed implant for cases of significant bone loss, deformity correction, or failed arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…At the 5-year follow-up, the longest recorded follow-up in the literature, the patient was found to exhibit osseous integration on radiographic imaging with Patient Reported Outcome Measures indicating high function and negligible pain 6 . Adams and Danilkowicz 7 implemented the use of a custom, 3D printed titanium implant for talonavicular joint salvage in the setting of navicular fracture with maintained radiographic alignment, successful arthrodesis to the cuneiforms, function of the talonavicular joint, and continued employment at 4 years of follow-up. Dekker et al 8 reported on 15 consecutive patients who received a custom, 3D printed implant for cases of significant bone loss, deformity correction, or failed arthrodesis.…”
Section: Discussionmentioning
confidence: 99%